Automotive & Geomatica GNSS, SLAM e V2X le chiavi del futuro delle macchine autonome - Santarsiero, Domenico (GEOmedia, 2019)
The convergence of technologies has always been a natural path of growth linked to the change in the general paradigms of society, in a more or less accentuated, but unavoidable way. This is one of those times when paradigms are rapidly changing, and the convergence of technologies proves it once again. We are talking about automatic mobility, about the machine of the future, about the time that each of us will have available, not having to drive the personal transport.